1992
DOI: 10.1515/cclm.1992.30.12.809
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Bone Alkaline Phosphatase, CA 15-3 and CEA in the Detection of Bone Metastases During the Follow-Up of Patients Suffering from Breast Carcinoma

Abstract: Summary: After the introduction (1, 2) and methodical evaluation (3, 4) of a new method for the quantitative measurement of the bone isoenzyme of alkaline phosphatase (test-combination bone alkaline phosphatase, Boehringer Mannheim), we started a retrospective clinical study for the follow-up investigations of breast cancer patients. Our aim was to establish the significance of the routinely used tumour markers, CEA and CA 15-3, in combination with bone alkaline phosphatase for the early detection of metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 1 publication
1
13
1
1
Order By: Relevance
“…Our results show a high discriminating power of bone alkaline phosphatase values for differentiating between patients with and those without bone metastases, in contrast to the results of van Hoff et al (10) as well as Stieber et al (11) who found no such statistically significant difference. This difference may be due to the different localization of the primary tumours as well as due to the different character of the bone lesions (osteoblastic, osteolytic and mixed, respectively).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results show a high discriminating power of bone alkaline phosphatase values for differentiating between patients with and those without bone metastases, in contrast to the results of van Hoff et al (10) as well as Stieber et al (11) who found no such statistically significant difference. This difference may be due to the different localization of the primary tumours as well as due to the different character of the bone lesions (osteoblastic, osteolytic and mixed, respectively).…”
Section: Discussioncontrasting
confidence: 99%
“…In patients with prostate cancer it has already been shown that serial measurements of the urinary excretion of pyridinium cross-links are suitable for monitoring of clinical progression (29); the same applies to the determination of bone alkaline phosphatase activity in patients with breast cancer (11). Moreover, in patients with tumour-induced osteolysis the urinary excretion of pyridinium cross-links may be a useful quantity for monitoring therapy with agents inhibiting osteoclast activity (e.g., bisphosphonates) (19).…”
Section: Discussionmentioning
confidence: 99%
“…56) ALP, an orthophosphoric monoester phosphorylase, is found to be the most sensitive marker in metastasis. 57) Stieber et al, 58) have shown that determination of ALP is a rapid method to detect progressive disease in breast cancer and serves to gauge the localization of metastatic diseases. The elevated ALP activity in mammary carcinoma is attributed to the secondary malignancies of mammary carcinoma that metastasizes to bone and liver.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally agreed that tumour markers in breast cancer patients are not a tool for primary diagnosis, because of their low sensitivity and specificity (Tondini et al, 1989;Fateh-Moghadam and Stieber, 1993;Lamerz et al, 1993). Their use for early detection of metastases seems to be promising (Lamerz et al, 1991;Stieber et al, 1992;Vizcarra et al, 1994;O'Hanlon et al, 1995) and their use for measuring therapeutic response in metastatic disease is widely accepted (Tondini et al, 1988;Dnistrian et al, 1991;Robertson et al, 1991;Safi et al, 1991). Many studies tried to assess the prognostic role of these tumour markers (some analysed in serum, some in tissue), but most of them had low patient numbers or short follow-up periods, and used only univariate analyses (Myers Tormey and Waalkes, 1978;Bezwoda et al, 1981;Mansour et al, 1983;Kallioniemi et al, 1988;Hammer et al, 1992;O'Hanlon et al, 1995).…”
Section: Discussionmentioning
confidence: 99%